Experimental evaluation of glass fiber composite reinforced with cellulose nanoparticles. (2021) - Sundareswaran, Santhosh Kumar; Rajendran, Balaji; Dinesh Kumar, P.K.
Abstract: This study aims to improve the mechanical properties such as tensile strength, flexural strength, impact energy and fracture toughness of a Glass Fiber Reinforced Polymer (GFRP) composite laminate by reinforcing it with Cellulose Nano-Crystals (CNC) for the application of stow bin and the sub floor box on the fuselage of the aircraft. The epoxy matrix of the GFRP composite was reinforced with Cellulose Nano Crystals by the sonication process, SEM images were taken to study the mixing characteristics of CNC with GFRP laminate. Three specimens have been prepared with varying quantities of CNC dispersion in the matrix. The specimen with the code (GE) was not reinforced with CNC. Whereas the specimen (CGECNC-1) and the specimen (CGECNC-2) was reinforced with 10% wt. And 20% wt. of CNC in its matrix, respectively. The experimental results have been obtained from the load–displacement plot from each test. These results revealed that the specimen reinforced with 10% wt. CNC had improved tensile strength, flexural strength, impact energy and fracture toughness when compared to the other two specimens. The mechanical properties improved with 10% wt. CNC whereas it decreased with the reinforcement of 20% wt. CNC. In 20% wt. The excess amount of CNC tends to decreases the density of resin which induces the poor bonding between fiber and resin. The elasticity of the material decreases with an increase in the CNC.